2017
DOI: 10.1038/pr.2016.274
|View full text |Cite
|
Sign up to set email alerts
|

Validity and intraobserver reliability of three-dimensional scanning compared with conventional anthropometry for children and adolescents from a population-based cohort study

Abstract: Scanning is faster, requires less intensive staff training and provides more information. It can be used in an epidemiologic setting with children and adolescents but some measurements should be considered with caution due to reduced agreement with conventional anthropometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Other methods, such as dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance analysis, represent interesting options of estimating "internal" tissue distribution in the human body. Threedimensional (3D) whole-body laser scanning provides another promising technique for evaluating "external" body shape by granting the opportunity to assess dozens of anthropological body measures at once with high accuracy and within only a few seconds of time 9 . Body scanning is utilized in medical application, for example, for cosmetic and reconstructive surgery 10,11 , and increasingly in health research to study anthropometry of hundreds to thousands of participants in epidemiological cohort studies 9,12 to assess their possible relevance for health risk prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods, such as dual-energy X-ray absorptiometry (DXA) and bioelectrical impedance analysis, represent interesting options of estimating "internal" tissue distribution in the human body. Threedimensional (3D) whole-body laser scanning provides another promising technique for evaluating "external" body shape by granting the opportunity to assess dozens of anthropological body measures at once with high accuracy and within only a few seconds of time 9 . Body scanning is utilized in medical application, for example, for cosmetic and reconstructive surgery 10,11 , and increasingly in health research to study anthropometry of hundreds to thousands of participants in epidemiological cohort studies 9,12 to assess their possible relevance for health risk prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Beside widespread commercial applications like apparel design and ergonomics [1,2], body scanning is increasingly utilized in medial context, e.g. for cosmetic and reconstructive surgery [3,4], and recently in medical and health research to study anthropometry of hundreds to thousands of participants in large cohort studies with high accuracy [5,6]. These new and amended data are expected to improve the diagnostics of many diseases, however, current applications usually don't consider the whole information provided by the set of body measures and, instead, use only a small part of them to estimate simple body indices such as body mass index (BMI) or waist-to-hip circumference ratio (WtH) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Concordance correlation coefficients (CCCs) were calculated to assess validity. Overall CCCs (OCCCs) were used to analyze intraobserver reliability (1).…”
mentioning
confidence: 99%
“…At the same time, neck and thigh circumference showed a "good" (CCC ⩾ 0.7) and head circumference a "low" (CCCo0.5; flipping a coin!) degree of concordance over the complete study population (1). They thus concluded that scanning can be used in an epidemiologic setting with children and adolescents, but some measurements should be considered with caution due to reduced agreement with conventional anthropometry (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation